The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/ijmce-11-2019-0107
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of aspiring school principals receiving coaching as part of a leadership development programme

Abstract: PurposeThis paper adds depth to our understanding of how coaching works by exploring the experiences of 14 aspiring school principals who received one-to-one leadership coaching as part of a leadership development programme.Design/methodology/approachThis study adopts a phenomenological approach. Individual semi-structured interviews were conducted with the participants. Thematic analysis was used to code the data and identify themes.FindingsThis paper reports on four themes based on the experiences of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…More positively, we have also witnessed and reported (Hobson, 2021;Lucey and van Nieuwerburgh, 2020;van Nieuwerburgh et al, 2020), as have others (e.g. Dreer, 2021;K apl ar-Kod acsy and Dorner, 2020;Kutsyuruba and Godden, 2019), effective coaching and mentoring to be helpful means of mitigating detrimental impacts of the GERM on educators and other professionals.…”
Section: Ethical Coaching and Mentoring In Educationsupporting
confidence: 73%
“…More positively, we have also witnessed and reported (Hobson, 2021;Lucey and van Nieuwerburgh, 2020;van Nieuwerburgh et al, 2020), as have others (e.g. Dreer, 2021;K apl ar-Kod acsy and Dorner, 2020;Kutsyuruba and Godden, 2019), effective coaching and mentoring to be helpful means of mitigating detrimental impacts of the GERM on educators and other professionals.…”
Section: Ethical Coaching and Mentoring In Educationsupporting
confidence: 73%
“…The positive emotions of the coaching experience as expressed by the beginning principals and the principal-trainers are similar to research elsewhere (Bloom et al, 2005;Cherkowski and Walker, 2018;Grant, 2014;James-Ward, 2013;Keyes, 2003;Kutsyuruba et al, 2019;Lackritz et al, 2019;Lochmiller, 2014Lochmiller, , 2018Lowery, 2019;Ng, 2005;van Nieuwerburgh et al, 2020;Wise and Cavazos, 2017;Wise and Jacobo, 2010). The beginning principals appreciated the safe space when coached, and this sentiment concurs with the works of other researchers (Lochmiller, 2018;Netolicky, 2016;Robertson, 2009;van Nieuwerburgh et al, 2020;Wise and Hammack, 2011). They articulated how their coaches supported them in raising self-awareness and enabling them to reflect deeper, analyzing issues from different perspectives and, in the process, availing themselves to the different possibilities for future actions.…”
Section: Discussionsupporting
confidence: 84%
“…In leadership development, principals can be supported by leadership coaches who are experienced principals themselves (Bloom et al, 2005;van Nieuwerburgh et al, 2020;Wise and Jacobo, 2010). The culture of shared understanding between first-time principals and the experienced principals as coaches can be helpful as the focus is on the common ground of school leadership (Brothers, 2005;James-Ward, 2013;Lochmiller, 2014Lochmiller, , 2018.…”
Section: Coaching For Leaders In Singapore Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies indicated the relationship between school leadership and school overall performance. High-performing school leaders play in the ways of school performance (Nieuwerburgh et al 2020). These include selecting the right persons as school leaders and further developing them to become immensely important toward the school performance.…”
Section: High-performing School Leadersmentioning
confidence: 99%